Bracketing sustainability: Carbon footprinting March Madness to rethink sustainable tourism approaches and measurements. (10th October 2021) - Cooper, J.A.; McCullough, Brian P.
Abstract: Amidst a backdrop of a global climate emergency, tourism continues to contribute to Earth's carbon footprint. In recognition of the negative environmental impacts of sport and event tourism, this study quantifies the carbon footprint of the 2019 National Collegiate Athletic Association Men's Basketball Tournament by considering the travel of fans and teams, food, waste, lodging, and stadium operations. The footprint is approximated at 210 million kilograms of carbon dioxide equivalents. Broken down, this equates to about 500 kg per participant. Travel is responsible for nearly 80 percent of that total which underscores the positive relationship between distance traveled and greenhouse gasses emitted in tourism. This paper presents a valuable linear model by which carbon footprints can be calculated with accessible data. This will, in turn, allow for the democratization of sustainability models for industries and organizations to introspectively quantify their environmental impact as an initial assessment for internal purposes or comparison to outside audits. This study's results demonstrate the need to make mega sport-tourism events like March Madness more sustainable. However, this can only be done by tourism managers closing the environmental value-action gap that too often manifests as inaction. By leveraging quantitative frameworks such as this study's methodology, sport and event managers can more easily use readily available data to evaluate their event's environmental impacts and thus begin to actionably mitigate their negative contributions to global climate change in more targeted ways. Highlights: A novel, data-poor approach to carbon footprinting sport tourism. A case study of emissions caused by tourism activities of participants and spectators of the NCAA Basketball Tournament. Event and sport practitioners should implement more sustainable policies, practices, and models of tourism. Sport and event practitioners can leverage this model with internal data to estimate carbon footprinting for their events.